Comparison of identity crisis in adolescents with cancer and diabetes, a cross-sectional study - Mohammadjavad Hassani; Fateme Mohammadi; Salman Khazaie; Marzie Effat Panah; Arash Khalili (BMC Pediatrics)
Abstract Background Identity crisis during adolescence is an important issue; on the other hand, adolescents suffering from chronic diseases such as cancer and diabetes increase the challenges of this period and the importance of successfully overcoming it. The present study was conducted with the aim of comparing identity crisis in adolescents with cancer and diabetes. Methods This cross-sectional study was conducted from August 2022 to November 2024 on 300 adolescents within the age range of 15–17 years with cancer and diabetes (150 in each group) who were selected with convenience sampling. Data were collected using demographic characteristics and identity crisis questionnaires. Data analysis was performed using SPSS-22 software. The significance level in all tests was less than 0.05. Results The mean of identity crisis in adolescents with cancer and diabetes was 130.82 ± 2.38 and 123.49 ± 2.45, respectively. The mean total score of identity crisis and scores of areas of dissatisfaction with life, hopelessness, sadness (p < 0.001), aimlessness, worthlessness, and anxiety (p < 0.01) were higher in adolescents with cancer than in those with diabetes. The variables of the age of adolescents, cancer duration, family income, and education of the mother predicted 56.63% of the variance changes in the identity crisis of adolescents with cancer and 55.76% of the variance changes in the identity crisis of adolescents with diabetes. Conclusion Identity crisis is one of the important challenges in the lives of adolescents with cancer and diabetes. These adolescents experience moderate to severe identity crises, and this condition is more common in adolescents with cancer. Clinical trial number Not applicable.